Poloxamer-188 and citicoline provide neuronal membrane integrity and protect membrane stability in cortical spreading depression. (2nd December 2015) - Yıldırım, Timur; Eylen, Alpaslan; Lule, Sevda; Erdener, Sefik Evren; Vural, Atay; Karatas, Hulya; Ozveren, Mehmet Faik; Dalkara, Turgay; Gursoy-Ozdemir, Yasemin
Abstract : Under pathological conditions such as brain trauma, subarachnoid hemorrhage and stroke, cortical spreading depression (CSD) or peri-infarct depolarizations contribute to brain damage in animal models of neurological disorders as well as in human neurological diseases. CSD causes transient megachannel opening on the neuronal membrane, which may compromise neuronal survival under pathological conditions. Poloxamer-188 (P-188) and citicoline are neuroprotectants with membrane sealing properties. The aim of this study is to investigate the effect of P-188 and citicoline on the neuronal megachannel opening induced by CSD in the mouse brain. We have monitored megachannel opening with propidium iodide, a membrane impermeable fluorescent dye and, demonstrate that P-188 and citicoline strikingly decreased CSD-induced neuronal PI influx in cortex and hippocampal dentate gyrus. Therefore, these agents may be providing neuroprotection by blocking megachannel opening, which may be related to their membrane sealing action and warrant further investigation for treatment of traumatic brain injury and ischemic stroke.